2022
DOI: 10.3390/insects13020212
|View full text |Cite
|
Sign up to set email alerts
|

A Route to Translate a Silk-Based Medical Device from Lab to Clinic: The Silk Biomaterials Srl Experience

Abstract: The medical device is a nerve conduit entirely made of Bombyx mori silk fibroin. It is a tubular scaffold used for repairing peripheral nerve gaps, whose function is to protect the severed nerves and to favor their natural healing process. As any implantable medical device, the conduit must perform its function without causing adverse effects to the patient, meaning that it must be compliant with a range of regulations aimed at evaluating the risks related to the constituent materials and the manufacturing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…considering a silk fibroin scaffold sample of mass (M) equals to 0.0985 g, geometry of: 1.8 cm in length, inner diameter of 0.5 cm and outer diameter of 0.625 cm and density of 1.35 g/cm 3 ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…considering a silk fibroin scaffold sample of mass (M) equals to 0.0985 g, geometry of: 1.8 cm in length, inner diameter of 0.5 cm and outer diameter of 0.625 cm and density of 1.35 g/cm 3 ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…After tissue equilibration, time necessary to filter 10 mm 3 of water was measured. Scaffold porosity was evaluated according to the following formula (17):…”
Section: Scaffolds Characteristics and Preparation/coatingmentioning
confidence: 99%
“…Currently, there are various processing forms for SF: scaffolds, sponges, or films, etc. [ 35 , 36 , 37 , 38 , 39 , 40 ]. It has been shown that the biocompatibility feature is influenced by the purification method and the purification process.…”
Section: Sf Key Propertiesmentioning
confidence: 99%
“…Furthermore, this issue contains numerous articles that address these novel applications and cover both the general role of silk fibroin in biomedicine [6] and methods for creating hybrid materials, for instance, by adding nanoparticles [7]. The paper by Bassani et al [8] examined particular devices, such as silk nerve conduits, in a study case illustrating how research findings can be translated into medical products for use in clinical settings.…”
mentioning
confidence: 99%